SAT0408 UTILITY OF CAROTID ULTRASOUND AND FRAMINGHAM RISK SCORE ON DISCRIMINATING CORONARY ARTERY DISEASE IN PATIENTS WITH PSORIATIC ARTHRITIS (PsA). (2nd June 2020) - Cheng, I. T.; Wong, K. T.; Li, E.; Wong, P. C.; Lai, B. T. L.; Yim, C. W.; Ying, S. K. Y.; Kwok, K. Y.; Li, M.; Li, T. K.; Lee, J. J. W.; Lee, A. P. W.; et al.
Abstract : Background: While carotid ultrasound (US) has been advocated for cardiovascular (CV) risk screening in patients with rheumatoid arthritis as various traditional scores underestimate CV risk, whether subclinical carotid atherosclerosis (SCA) is associated with coronary atherosclerosis on coronary computed tomography angiography (CCTA) in patients with psoriatic arthritis (PsA) remains uncertain. Objectives: This study aimed to identify carotid US parameters which can discriminate PsA patients with coronary artery disease (CAD) and obstructive CAD (O-CAD), and determine the utility in combination with Framingham Risk Score (FRS). Methods: Ninety-one PsA patients (56 males; age: 50±11years, disease duration: 9.4±9.2years) without overt CV diseases were recruited. Carotid intima-media thickness (cIMT), presence of plaque and total plaque area (TPA) were determined by high-resolution US. CAD was defined as the presence of any coronary plaque on CCTA. O-CAD was defined as >50% stenosis of the lumen. FRS <10% indicates low CV risk, 10-19% indicates intermediate risk while ≥20% indicates high risk (1). Results: Thirty-five (38%) patient had carotid plaque. Fifty-five (60%) patients had CAD and 9 (10%) patients had O-CAD. 53 (58%), 25 (17%) and 13 (14%) were classified as low, moderate and high CV risk according to the FRS respectively. FRS underestimated the CV risk as only 11/55 (20%) of subjects with CAD were correctly identified as having high CV risk by FRS (Figure 1 ). Fifteen patients out of 53 (28%) with low CV risk based on FRS were reclassified as high CV risk by the presence of carotid plaque. Nine out of these 15 (60%) had CAD and 1/15 (6.7%) had O-CAD. Concerning the carotid ultrasound parameters, cIMT (mean and maximum) and TPA were increased in both the CAD+ and O-CAD+ group compared to those without CAD or O-CAD (Table 1 ). Multivariate logistic regression analysis revealed that mean cIMT (OR=1.06, 95% CI:1.01-1.11, p =0.013) was an independent explanatory variables associated with CAD. Meanwhile, mean cIMT (OR=1.06, 95%CI: 1.01-1.11, p =0.013) maximum cIMT (OR=1.06, 95%CI: 1.00-1.13, p =0.043), and TPA (OR=1.55, 95%CI: 1.01-2.36, p =0.043) were independent explanatory variables associated with O-CAD after adjusting for covariates. Based on Receiver Operating Curve (ROC) analysis, an optimal cut off for FRS at 5% and mean cIMT at 0.62mm yield 63% sensitivity and 73% specificity for the presence of CAD (AUC: 0.71, p =0.001). Conclusion: Increased cIMT and TPA were associated with CAD and O-CAD in PsA patients while the presence of carotid plaque alone was insufficient to discriminate patient with or without CAD. A combination of US parameters should be considered for CV risk stratification in patients with PsA. References: [1]Ford ES et al., J Am Coll Cardiol . 2004;43(10):1791-6. Disclosure of Interests: Isaac T. Cheng: None declared, Ka Tat Wong: None declared, Edmund Li: None declared, Priscilla C Wong: None declared, Billy Tin Lok Lai: None declared, Cheuk Wan Yim: None declared, Shirley King Yee Ying: None declared, Kitty Yan Kwok: None declared, Martin Li: None declared, Tena K. Li: None declared, Jack Jock Wai Lee: None declared, Alex Pui Wai Lee: None declared, Lai-Shan Tam Grant/research support from: Janssen, Pfizer, Novartis, Speakers bureau: Abbvie, Lilly, Sanofi